Acceptance of repeat population-based voluntary counselling and testing for HIV in rural Malawi. Issue 2 (16th October 2008) - Obare, F; Fleming, P; Anglewicz, P; Thornton, R; Martinson, F; Kapatuka, A; Poulin, M; Watkins, S; Kohler, H-P
Abstract : Objective: To examine the acceptance of repeat population-based voluntary counselling and testing (VCT) for HIV in rural Malawi. Methods: Behavioural and biomarker data were collected in 2004 and 2006 from approximately 3000 adult respondents. In 2004, oral swab specimens were collected and analysed using ELISA and confirmatory Western blot tests, while finger-prick rapid testing was done in 2006. We used cross-tabulations with χ 2 tests and significance tests of proportions to determine the statistical significance of differences in acceptance of VCT by year, individual characteristics and HIV risk. Results: First, over 90% of respondents in each round accepted the HIV test, despite variations in testing protocols. Second, the percentage of individuals who obtained their test results significantly increased from 67% in 2004, when the results were provided in randomly selected locations several weeks after the specimens were collected, to 98% in 2006 when they were made available immediately within the home. Third, whereas there were significant variations in the sociodemographic and behavioural profiles of those who were successfully contacted for a second HIV test, this was not the case for those who accepted repeat VCT. This suggests that variations in the success of repeat testing might come from contacting the individuals rather than from accepting the test or knowing the results. Conclusions: Repeat HIV testing at home by trained healthcare workers from outside the local area, and with either saliva or blood, is almost universally acceptable in rural Malawi and, thus, likely to be acceptable in similar contexts.